The Example-Problem-Based Learning Model: Applying Cognitive Load Theory. (3rd July 2015) - Jalani, Noor Hisham; Sern, Lai Chee
Abstract: Cognitive Load Theory (CLT) suggests that learning best takes place in a situation that is equivalent to individual cognitive design. Thus, this article proposes a learning model called Example-Problem-Based Learning (EPBL) which is a combination of two learning strategies: worked-examples and problem-solving. This teaching method guides students to go through several cognitive developments. At the early stages of knowledge acquisition, novice students benefit more from worked-examples, which is a model of problem-solving. After they have gained sufficient knowledge, worked-examples may no longer be appropriate because the positive effects of worked-examples will be lost. Therefore, learning through problem-solving should be applied since students have already equipped themselves with profound domain knowledge. Established in an experiment conducted, the EPBL teaching method enhances students' knowledge acquisitions, learning transfer, and mental effort during learning, as well as increasing their learning efficiency.